Clinical utility of methicillin-resistant Staphylococcus aureus nasal polymerase chain reaction (PCR) assays beyond respiratory infections. Issue 1 (30th June 2022) - Noeldner, Haley M.; Bliek, Zachary J.; Jones, Nephi E.; Prusa, Ryan D.; Wilkinson, Melissa S.; Bushman, Amanda M.; Rosa, Rossana
Abstract: We estimated the predictive value of methicillin-resistant Staphylococcus aureus (MRSA) nasal polymerase chain reaction (PCR) for blood, bone, and soft-tissue cultures. The specificities were 88.8%, 88.5%, and 92.7% for all cultures, blood cultures, and bone and soft-tissue cultures respectively, and the negative predictive values were 99.3%, 99.8%, and 92.7% respectively.